BIODIVERSITAS MOLUSKA (GASTROPODA DAN BIVALVIA) DI KAWASAN MANGROVE PANTAI CEMARA, LOMBOK BARAT - Baiq Melinda Utari; Munawir Sazali (Universitas Lambung Mangkurat, 2026)
The mangrove area of Cemara Beach is an ecosystem that plays an important role in supporting life, including molluscs. This study aims to examine the biodiversity of molluscs in the area and to develop educational poster materials for the Animal Systematics course. The research design used is exploratory with a random sampling method at seven observation stations selected at 30-meter intervals. Samples were collected using tools such as plankton nets and hoes for digging substrate. Environmental parameters were measured using a salinity refractometer for salinity and a pH meter for water pH. The collection data were analysed descriptively to illustrate the diversity of mollusc species found. The Cemara Beach mangrove area has high mollusc biodiversity with Simpson index values of 0.905–0.9224 (very high), Shannon-Wiener 2.468–2.591 (moderate), and evenness 0.8426–0.9533 (very even). Low dominance values (0.07764–0.09503) indicate that no species dominate. Environmental conditions such as temperature (28.5–29°C) and pH (7.6–8.0) support the stability of the mollusc ecosystem. Statistical tests showed significant differences between stations (p = 0.000752), proving that local variations affect community structure.